Similar lymphocytic infiltration pattern in primary breast cancer and their corresponding distant metastases - Sobottka, Bettina (Oncoimmunology, 2016)
Tumor infiltrating lymphocytes in primary breast cancer (TIL) are acknowledged measures of disease free survival (DFS) in adjuvant and neoadjuvant settings. Little is known about the biology of metastasis infiltrating lymphocytes (mTIL) although the local immunity of the metastatic site may critically influence the infiltrate composite. To address this question, we compared mTIL with their matched TIL in 87 breast cancer patients and their corresponding distant metastasis at four different anatomical locations. Sections of surgical specimen were immunohistochemically analyzed for CD4(+), CD8(+) and CD20(+) lymphocytes in three different tumor compartments: intratumoral lymphocytes (iTIL) defined as lymphocytes in direct contact with breast cancer cells, stromal lymphocytes (sTIL) located within the intratumoral stromal tissue and invasive-margin lymphocytes (imTIL). Overall, we found fewer (p < 0.001) mTIL than TIL. Within the tumor compartments, imTIL were more frequent than sTIL and iTIL both within metastases and the matched primary tumors (PT) (p < 0.001). CD4(+) T cells were more numerous than CD8(+) T cells and CD20(+) B cells (p < 0.001). There was a similar pattern in PT and their corresponding metastasis. Only patients with brain metastases differed from the others displaying less CD20(+) B cells at the infiltrative margin of the PT (p < 0.05). In summary, mTIL were significantly reduced within metastases but still mirrored the infiltrate pattern of the PT, interestingly regardless of the metastatic anatomical locations investigated. Our results suggest that the PT assigns the infiltrating lymphocyte pattern resumed at the metastatic site.